2017
DOI: 10.5539/res.v9n3p117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intellectual Capital and Work Behavior in Supporting Lecturer’s Performance

Abstract: Muhammadiyah Universities in South Sulawesi face the challenges of competitiveness, quality of human resources and lecturer's on Tridharma performance in the field of education and teaching, research and scientific publications, and dedication to the community and other support activities.This research aims at reconstructing the development of intellectual capital through Al-Islam Kemuhammadiyaan values approach. So as to create good work behavior in order to support the university's performance on Tridharma.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In Indonesia, lecturers with master's degrees have to increase their educational qualifications to develop their academic careers (Astuti et al, 2013). This higher qualification is needed because intellectual capital affects work behavior and lecturer performance significantly (Rahim et al, 2017). Negotiation skill is also essential in academic career development for lecturers.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, lecturers with master's degrees have to increase their educational qualifications to develop their academic careers (Astuti et al, 2013). This higher qualification is needed because intellectual capital affects work behavior and lecturer performance significantly (Rahim et al, 2017). Negotiation skill is also essential in academic career development for lecturers.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the study results found that the organization's success will increasingly depend on teamwork rather than on prominent individuals (D 'Netto et al, 2014). In addition to teamwork management, culture diversity also affects the ability of research staff with a culture to complement and share knowledge (Dollwet & Reichard, 2014); (Jusriadi, Edi, 2019); (Maurer et al, 2017); and (Rahim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%